Improving quality of frozen-thawed bull spermatozoa via in vitro supplementation with alpha-linolenic and docosahexaenoic acid - Kaka, Asmatullah (2015)
Animal production has been modernized through cryopreservation. However,cryopreservation decreases the quality and fertility of bull sperm by impairing its normal functions due to thermal, oxidative and osmotic changes and re-distribution of lipid bonding. Therefore, the present study was conducted to test, if supplementation of semen extenders with fatty acids and antioxidants could improve the quality of frozenthawed of bull semen. Semen samples from three fertile beef bulls were collected twice a week by an electro ejaculator. After collection, semen samples were brought to the laboratory for initial evaluation. Ejaculates with motility ≥ 70% and normal morphology and viability ≥ 80% were processed for cryopreservation. Ejaculates were extended in Tris and BioXcell® extenders containing 0 (control), 3, 5, 10 and 15ng/ml of docosahexaenoic acid (DHA) and α-linolenic acid (ALA). As the fatty acids are insoluble in water, 0.05% ethanol was added as a solvent. Extended samples were initially incubated at 37oC for 15 minutes to allow absorption of ALA by the sperm membrane, and then chilled for 2 hours, followed by packaging into 0.25ml straws with 20 x 106 sperm per straw. The straws were placed 3cm above the surface of liquid nitrogen for 10 minutes and finally immersed into liquid nitrogen for storage. After 24 hours, straws were thawed and evaluated for sperm motility using a computer assisted semen analyzer (CASA), membrane functional integrity (hypo-osmotic swelling test), viability, morphology, acrosome integrity (eosin-nigrosin stain), DNA integrity (comet assay), fatty acid composition (gas chromatography), lipid peroxidation (thiobarbituric acid reactive substances, TBARS) and superoxide dismutase (SOD assay). Data of all the parameters was analyzed with SAS 9.2 version with the general linear model (GLM) and Duncan multiple range test (DMR). Results showed that adding ALA into BioXcell® and Tris semen extender improved post- thawed quality of bovine semen. Frozen-thawed sperm motility, morphology, viability, morphology, acrosome integrity, DNA integrity and ALA concentration were improved significantly in treated groups compared to control. Uptake was observed to be linear in relation to ALA concentration added. A concentration of 5ng/ml of ALA was found to be the optimum level for improved semen cryopreservation using Bioxcell® and Tris extender along with tolerable Lipid peroxidation (LPO) reactions and amount of MDA production. DHA supplementation into BioXcell® and Tris extenders also produced positive effects on freezing quality of bull sperm. Frozenthawed sperm motility, morphology, viability, morphology, acrosome integrity, DNA integrity and DHA concentration were significantly improved at 3ng/ml and 10ng/ml of DHA in BioXcell® and Tris extenders, respectively. Docosahexaenoic acid supplementation produced higher lipid peroxidation rate as compared to ALA but it did not affect sperm quality. Superoxide dismutase enzyme was also improved in both ALA and DHA supplementations. A combined effect of DHA and ALA into BioXcell® and Tris extenders however decreased frozen-thawed quality of the bull sperm. Frozenthawed sperm motility, morphology, viability, morphology, acrosome integrity and DNA integrity were decreased in treated groups compared to control. Fatty acid and SOD improved positively but MDA was produced in large quantity that decreased quality of sperm. In the last experiment 5ng/ml of ALA level from Experiment 1 and 3 and 10ng/ml of DHA from Experiment 2 were combined with 0.2, 0.4 and 0.8mM of α-tocopherol to evaluate the effect of fatty acids and antioxidant combination on post thawed quality of bull sperm. Results showed that combination of ALA and α-tocopherol improved frozen-thawed quality compared to control in both BioXcell® and Tris extenders. Significantly higher values were obtained at 5ng/ml of ALA and 0.2mM of α-tocopherol in BioXcell® extender and 5ng/ml ALA with 0.4mM α-tocopherol in Tris extender. DHA also improved frozen-thawed quality in both BioXcell® and Tris extenders, with significant improvement at 3ng/ml of DHA with 0.5mM α-tocopherol and 10ng/ml of DHA with 0.8mM α-tocopherol in BioXcell® and Tris extenders respectively. Fatty acid level was improved, MDA and superoxide dismutase production was decreased. In conclusion, combination of ALA and DHA decreased quality of frozen-thawed bull semen. However, addition of ALA at 5ng/ml and DHA at 3 and 10ng/ml in combination with α-tocopherol improved quality of frozen-thawed of bull semen in Tris and BioXcell® extenders respectively.